Relative effectiveness of phonological and morphological awareness training on L2 word reading in EFL children. (August 2016) - Li, Yi-syuan; Chen, Shu-hui
Abstract: This study investigates the relative effectiveness of phonological and morphological awareness training on Taiwanese EFL children's English word reading, involving real and pseudo-words with morphologically simple and complex structures, through an experimental design with three groups of 60 children. One intervention group received phonological awareness training while the other received morphological awareness training. The intervention lasted 40 min per week for 12 weeks. The control group received a regular program without intervention. The three groups had similar initial English proficiency levels before the intervention. Data were collected by assessing the participants' English word reading before and after the intervention and were analyzed by ANOVAs. Results indicated that both intervention programs significantly improved posttest word reading to a similar extent, irrespective of word type and word structure. Nevertheless, only the phonological training program yielded a significantly better effect on the posttest L2 word reading than the regular instruction. Irrespective of word structure and group, the participants as a whole performed better in posttest real word than in pseudo-word reading. However, the phonological training displayed a significant better impact on pseudo-word than on real word reading, irrespective of word structure and test-time. The findings are discussed from psycholinguistic, literacy, and cross-linguistic perspectives.